The land question and sustainable development in South Africa: Issues and challenges - Wellington Didibhuku, Thwala (African Journal of Environmental Economics and Management, 2020)
Poverty and unemployment are problems that South Africa has not been able to overcome successfully. In the urban areas, poverty has led to the growth of informal settlements which are basically, but not necessarily so residential areas for the low-income groups. The most noted cause of informal settlements is high migration from rural areas by people who are in search of job opportunities and better living conditions than what is available in the rural areas. The march towards sustainable development in South Africa is taking many facets of people’s livelihoods and searches for multidimensional solutions to many problems. Thus, any discourse on sustainable development must take the land question into consideration since land is at the centre of a number of complex and very much-interrelated factors from social, political, economic and environmental factors of development. To this end, there is now a growing recognition of the centrality of land in the sustainable development process in South Africa and the Southern African region as witnessed by a number of regional initiatives and meetings. The quest for both socio-economic and bio-physical aspects of development requires that South Africa transcend a narrow sectoral focus and adopts a holistic viewpoint that is sensitive to the multiple linkages and interactions among environmental and social issues. The purpose of this work is to provide an overview and explore some of the issues that form the basis of the land question in South Africa. This work assessed the relationship between land and sustainable development.